2018
DOI: 10.1016/j.wasman.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing and optimizing sustainable measures for food waste prevention and management

Abstract: HighlightsThe waste hierarchy is not enough for prioritizing food waste prevention measures.The methodology proposed prioritizes measures using LCA and mathematical programming.The methodology identifies quick wins – actions with low cost and high impact avoided.The relevance of the weighting set used in the prioritization is limited.Targets for food waste prevention must be set at the level of environmental impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 24 publications
(33 reference statements)
2
67
0
3
Order By: Relevance
“…Furthermore, Koester et al (2018) concluded that costs incurred by the measure itself, namely the costs for implementing a measure, are rarely considered. Cristóbal et al (2018) further conclude there is only "limited knowledge on the evaluation of food waste prevention and management strategies including both economic and environmental dimensions" and that data on performance of measures is scarce.…”
Section: The Knowledge Gap Regarding the Performance Of Food Waste Mementioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, Koester et al (2018) concluded that costs incurred by the measure itself, namely the costs for implementing a measure, are rarely considered. Cristóbal et al (2018) further conclude there is only "limited knowledge on the evaluation of food waste prevention and management strategies including both economic and environmental dimensions" and that data on performance of measures is scarce.…”
Section: The Knowledge Gap Regarding the Performance Of Food Waste Mementioning
confidence: 97%
“…To our best knowledge, no reviews currently exist assessing the extent to which ecological impacts, monetary costs or savings, and efficiency of food waste measures are considered. Several authors have however stressed that, in case monetary aspects are taken into account, these tend to be restricted to the costs embodied in the food itself (based on for example retail prices), whereas disposal related costs are neglected (Rutten et al, 2013;Teuber and Jensen, 2016;Cristóbal et al, 2018;Koester et al, 2018). Furthermore, Koester et al (2018) concluded that costs incurred by the measure itself, namely the costs for implementing a measure, are rarely considered.…”
Section: The Knowledge Gap Regarding the Performance Of Food Waste Mementioning
confidence: 99%
See 1 more Smart Citation
“…The stakeholders showed a great interest in pointing out all sorts of difficulties that farmers, wholesalers, and supermarkets, as well as social entities, face when improving redistribution in the metropolitan region. Although the issue of food redistribution, as an acceptable alternative to food waste prevention and reduction, has been treated extensively in the literature [49,72,76,87,88], no previous study has referred to such difficulties (see Table 6).…”
Section: Redistributionmentioning
confidence: 99%
“…Cristóbal et al in Europe addressed the situation where a decision maker has to design a food waste prevention programme considering the limited economic resources and the results highlighted that to set the targets at the level of environmental impact is of importance instead of setting the targets at the level of avoided food waste generation (in mass) when FW prevention strategy requires planning [16]. While in China, Wen et al studied a case on evaluation of a sensor-based Internet of Things (IoT) network technology for restaurant food waste management.…”
Section: Generalized Managementmentioning
confidence: 99%